SHARIA MARKET AND THE IMPLEMENTATION OF SHARIA SELLING AND BUYING SYSTEM (A Case Study in Ulul Albab Market of Riau Province) - ardan mardan; idel waldelmi (Jurnal Ilmiah Ekonomi Dan Bisnis, 2020)
This study discussed on the implementation of sharia transactions in sharia markets. According to Wiroso, the dimension of sharia transactions can be seen in the brotherhood principle (ukhuwah), the justice principle (‘adalah), the benefit principle (mashlahah), the balance principle (tawazun), and the universalism principle (syumuliah). This study used survey method towards the merchants in Ulul Albab market by distributing questionnaires. The results were analyzed using descriptive analytical technique. According to the result of the study, it was found out that the implementation of sharia selling and buying system in the sharia market is appropriate in accordance with the assessment. It implemented all the five dimensions and the highest dimension proved to be the universalism dimension; meaning that the buying and selling activities employed to the whole society without restriction. Meanwhile, the lowest dimension was found to be the brotherhood dimension; meaning that the courteous manner and attitude towards familiar and unfamiliar customers were low.